Curriculum Management to Enhance Student Discipline and Academic Achievement at Ngunut - Bellyana, Audrey; Masrokan Mutohar, Prim (Studia Manageria, 2025)
This study aims to describe how curriculum management is implemented at State Junior High School 1 Ngunut to improve student discipline and academic achievement. The research focuses on how curriculum planning, implementation, and evaluation are integrated with the habituation of student discipline. This study employs a descriptive qualitative approach with data collected through interviews, observation, and documentation. Data were analyzed using the Miles and Huberman’s model, which includes data reduction, data display, and conclusion drawing. The results reveal that well-planned curriculum management integrated with habituation programs such as the 7 Habits of Great Indonesian Students, 5S, and Zero Late effectively fosters student discipline and enhances academic achievement. Curriculum supervision and evaluation are conducted continuously through classroom supervision and comprehensive assessments. In conclusion, collaborative, adaptive, and character-based curriculum management serves as an effective strategy for developing student discipline and improving academic performance at the junior high school level.